1956
DOI: 10.1136/adc.31.158.254
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Biochemical Study of Galactosaemia: A Possible Explanation of the Nature of the Biochemical Lesion

Abstract: The clinical syndrome of galactosaemia is now well known and more than 40 cases have been carefully described in the literature (Bell, Lindsay and Watson, 1950;Bray, Isaac and Watkins,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1959
1959
1998
1998

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Several authors (Goldbloom and Brickman, 1946;Komrower, Schwarz, Holzel and Golberg, 1956) have also drawn attention to the depression of blood glucose in patients taking milk-containing foods, and, although unable to relate this to any specific symptoms, considered that it contributed to the impairment of cell metabolism. Cox and Pugh (1954) recorded convulsions in a child taking a halfcream dried milk whilst Clay and Potter (1955) in an infant receiving a diet containing Casilan found that the fits stopped when mixed feeding was introduced and suggested that a metabolic cause was responsible for them.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors (Goldbloom and Brickman, 1946;Komrower, Schwarz, Holzel and Golberg, 1956) have also drawn attention to the depression of blood glucose in patients taking milk-containing foods, and, although unable to relate this to any specific symptoms, considered that it contributed to the impairment of cell metabolism. Cox and Pugh (1954) recorded convulsions in a child taking a halfcream dried milk whilst Clay and Potter (1955) in an infant receiving a diet containing Casilan found that the fits stopped when mixed feeding was introduced and suggested that a metabolic cause was responsible for them.…”
mentioning
confidence: 99%
“…The basis of this diet is a milk free cereal, Moll and Stransky used biscuit flour, and egg. Holzel (1954) was first to use a modified form of this diet in cases of galactosaemia, using the cereal Farex (Glaxo) as the base (Holzel, 1954;Komrower et al, 1956;Schwarz, Holzel and Komrower, 1958). This cereal now contains approximately 255% of lactose (Furnivall, 1958).…”
mentioning
confidence: 99%
“…The reported evidence that such metabolic disturbances exist in patients with RTA is circumstantial at best. RTA has been reported in association with such metabolic disorders as "glycogenosis" (9), cystinosis (10), galactosemia (11), Wilson's disease (12), Lowe's syndrome (13) and hereditary fructose intolerance (HFI) (14), but the relationship between the underlying metabolic abnormality and the acidification defect is unclear. Only in galactosemia and HFI is the causal biochemical defect known (15,16) and the resultant metabolic abnormality reversible and inducible experimentally (15,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In both disorders similar functional arnd structural abnormalities of the liver and kidney occur, which can be prevented and in some instances reversed by abstention from the specific hexose (17,18,34). In both disorders, persisting RTA, as well as reversible hexoseinduced proteinuria and aminoaciduria of a "nonoverflow" type, has been demonstrated (11,14,18,35,36). In two children with galactosemia, diagnosed just before death, increased amounts of Gal-1-P were measured in both renal and hepatic tissue (37).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation